Knowledge and perception of pregnant woman about COVID-19: impact on prenatal care practices (Research, Society and Development, 2023)
Objective: to understand how the knowledge and perceptions of pregnant women about COVID-19 influence their care practices. Methods: Qualitative, descriptive-exploratory study, with pregnant women in the 3rd trimester, aged 18 years or older and who underwent prenatal care at a Health Unit in Porto Alegre/RS, data were collected by telephone contact, through a semi-structured interview. Content analysis was performed. The research was approved by the Research Ethics Committee of Grupo Hospitalar Conceição (GHC). Results: Three categories emerged: knowledge about the new coronavirus, Care practices carried out by pregnant women in the face of the pandemic and Feelings of the pandemic. Final considerations: It was evident that pregnant women face challenges in the face of the economic impacts of social isolation and concern for the newborn. Thus, the continuity of prenatal care becomes fundamental in the context of the pandemic.